Analisis Perbandingan Website Digilib dengan Metode Penghitungan Usability Menggunakan Kuesioner SUS - Hafidz Pudyastawa Aji; Nur Rochmah DPA, S.T, M.Kom (Universitas Atma Jaya Yogyakarta, 2020)
Abstract: This study aims to analyze the comparison of Digilib websites at 3 universities. Digital Library is a media for storing book collections in digital form, as a means to facilitate visitors in accessing book collections. In improving services, universities X, Y, and Z have provided Digilib. Observation results indicate the number of Digilib visitors is still relatively small. Therefore quality evaluation on the Digilib website needs to be done. Quality evaluation on the Usability aspect is carried out using the existing assessment standards on the SUS questionnaire. Analysis and data processing of questionnaire results using SUS calculation. The results of the calculation of the average SUS score of 51 respondents from each university X, Y, and Z showed that, Digilib X had the highest SUS score of 58.2. The results of the score analysis indicate that the three websites have not met the usability aspect in terms of learnability. The SUS aspect analysis is used as a development reference to maximize the quality of Digilib services.Keywords: Quality Evaluation, Digital Library, Usability. Abstrak: Penelitian ini bertujuan menganalisis perbandingan website Digilib pada 3 universitas. Digital Library merupakan suatu media penyimpanan koleksi buku dalam bentuk digital, sebagai sarana untuk memudahkan pengunjung dalam mengakses koleksi buku. Dalam meningkatkan pelayanan, universitas X, Y, dan Z telah menyediakan Digilib. Hasil observasi menunjukkan jumlah pengunjung Digilib masih tergolong kecil. Oleh sebab itu evaluasi kualitas pada website Digilib perlu dilakukan. Evaluasi kualitas pada aspek Usability dilakukan menggunakan standar penilaian yang ada pada kuesioner SUS. Analisis dan pengolahan data hasil kuesioner menggunakan penghitungan SUS. Hasil perhitungan rata-rata skor SUS dari 51 responden masing-masing universitas X, Y, dan Z menunjukan bahwa, Digilib X memiliki skor SUS tertinggi yaitu 58,2. Hasil analisis skor menunjukkan bahwa ketiga website belum memenuhi aspek usability dari segi learnability. Analisis aspek SUS digunakan sebagai acuan pengembangan untuk memkasimalkan kualitas pelayanan Digilib.Kata Kunci: Evaluasi Kualitas, Digital Library, Usability.